# algebra

Can someone help me find value of x. please show step by step examples

6/x = 7/x+3

1. 👍 0
2. 👎 0
3. 👁 53
1. 6/x = 7/x+3

-1/x = 3

-1 = 3x

-1/3 = x

~~~~~~~~~~~~~~~~~~~~~
Check:
6/(-1/3) = 7(-1/3) + 3
-18 = -21 + 3

Yes!

1. 👍 0
2. 👎 0

## Similar Questions

1. ### Math

I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −

asked by Ryan on March 30, 2017
2. ### math

Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

asked by Anonymous on October 25, 2018
3. ### Math

William multiplied (-2x+1-3y)(-0.5x) and got the wrong solution. Review his work and identify the step in which William made his first error. Step 1 (-2x+1-3y)(-0.5x) Step 2 (-0.5x)(-2x-3y+1) Step 3 -0.5x(-2x)-0.5x(-3y)-0.5x(1)

asked by Cherie on June 10, 2019
4. ### Physics

Can someone please show me step by step how to normalize e^-5x in the interval (0, infinity)? I have read a lot of different books etc but need it explained to me in plain English or showed to me step by step because I am just not

asked by Tammy on September 16, 2011
5. ### Math (Check 2 answers please)

1. What is the value of b in the equation b + 8 = 13? A. 5**** B. 8 C. 13 D. 21 2. The steps below show the incomplete solution to find the value of x for the equation 7x − 3x − 4 = −1 + 21: Step 1: 7x − 3x − 4 = −1 +

asked by Alex on March 30, 2017
6. ### algebra

Can someone help me simplify this rational expression x^2-25 /x^2-3x-10 Please show step by step examples. thank you

asked by Alaska Diamond on July 28, 2013
7. ### Physics

I'm trying to rearange this 0 = Xo + 2^-1 a t^2 for t I've been told that it is (a^-1 2x)^(2^-1) but I do not see how please show me step by step how you get that 0 - Xo = Xo - Xo + 2^-1 a t^2 (-Xo = 2^-1 a t^2) a^-1 2 (a^-1

asked by Physics on June 23, 2009
8. ### Algebra help

f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is from my book: step 1: 0=x^3-4x^2-x+4 step 2: 0=x^2(x-4)+(-1)(x-4) step 3: 0=(x^2-1)(x-4) I know how to solve once I get to step 3, but in step 2, I don't know what

asked by Claure on June 16, 2009
9. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

asked by cv on October 21, 2013
10. ### algebra

Can someone show me step by step examples of simplifying 3√5/64 thank you

asked by Alaska Diamond on August 1, 2013

More Similar Questions